EFFECTIVE STRATEGIES FOR TEACHING FOREIGN LANGUAGES TO YOUNG LEARNERS - Toshmukhammedova Gulnoza Zayniddin kizi (Лучшие интеллектуальные исследования, 2024)
Teaching foreign languages to school learners is a valuable endeavor that opens doors to global communication and cultural understanding. To ensure effective language acquisition, educators must employ strategies that cater to the specific needs and learning styles of school-aged students. Young children have a remarkable capacity for language acquisition, and introducing them to a new language at an early age can yield long-lasting benefits. However, it requires careful planning, engaging instructional methods, and a supportive learning environment. In this article, we will explore some effective strategies for teaching foreign languages to young learners